KNOWLEDGE AND ATTITUDES REGARDING THE FULFILLMENT OF PREMARITAL NUTRITION AMONG ADOLESCENTS - Rosita, Siskana Dewi; Agustin, Kurnia; Mahmudah, Mutik (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
Basic Health Research (2018) reported the prevalence of chronic energy deficiency (CED) among non-pregnant and pregnant women of childbearing age in Indonesia by 14.5% and 17.3%, respectively. In addition, anemia in pregnant women increased from 37.1% to 48.9% in 2018. The health and nutritional status of pre-pregnant women can influence the nutritional status of children.This was a quantitative descriptive study with a cross sectional approach. The current study was conducted at MAN 1 Karanganyar in July-August 2023. The study samples involved 67 female respondents from class XII, who were selected using the Accidental Sampling technique. A questionnaire that had been tested for validity and reliability was applied as data collection instrument. Univariate and bivariate data analysis were performed by using the SPSS version 23.0 program. The results showed that the majority of respondents had a good level of knowledge on the fulfilment of pre-marital nutrition by 33 respondents (49.3%), and 40 respondents (59.7%) had a moderate level of attitude on the fulfilment of pre-marital nutrition. Keywords: knowledge, attitude, fulfilment of pre-marital nutrition